2014
DOI: 10.1038/srep03811
|View full text |Cite
|
Sign up to set email alerts
|

Bdellovibrio bacteriovorus Inhibits Staphylococcus aureus Biofilm Formation and Invasion into Human Epithelial Cells

Abstract: Bdellovibrio bacteriovorus HD100 is a predatory bacterium that attacks many Gram-negative human pathogens. A serious drawback of this strain, however, is its ineffectiveness against Gram-positive strains, such as the human pathogen Staphylococcus aureus. Here we demonstrate that the extracellular proteases produced by a host-independent B. bacteriovorus (HIB) effectively degrade/inhibit the formation of S. aureus biofilms and reduce its virulence. A 10% addition of HIB supernatant caused a 75% or greater reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 53 publications
2
84
1
4
Order By: Relevance
“…Крім того, деякі представники цих родів про вокують пневмонії, пієлонефрити, ендокардити, кістозні фібрози, зубний наліт та найчастіше пов'язані з катетер-асоційованими інфекціями [5,8,13,18,21].…”
Section: рисунок виживання вегетативних клітин (і) і спор (іі) в Suunclassified
“…Крім того, деякі представники цих родів про вокують пневмонії, пієлонефрити, ендокардити, кістозні фібрози, зубний наліт та найчастіше пов'язані з катетер-асоційованими інфекціями [5,8,13,18,21].…”
Section: рисунок виживання вегетативних клітин (і) і спор (іі) в Suunclassified
“…To sustain this kind of lifestyle Bdellovibrio genus is known to produce a large number of proteolytic enzymes and nucleases. Monnappa et al report that addition of 10% of HIB supernatant resulted in 75% or more reduction in S. aureus biofilm formation as well as dispersal of pre-formed biofilms [40]. LC-MS-MS analyses revealed that host independent B. bacteriovorus supernatant contained various proteases, including two significant serine proteases that were named as Bd2269 and Bd2321 [40].…”
Section: Role Of Extracellular Proteases From Other Prokaryotes In DImentioning
confidence: 99%
“…Monnappa et al report that addition of 10% of HIB supernatant resulted in 75% or more reduction in S. aureus biofilm formation as well as dispersal of pre-formed biofilms [40]. LC-MS-MS analyses revealed that host independent B. bacteriovorus supernatant contained various proteases, including two significant serine proteases that were named as Bd2269 and Bd2321 [40]. Authors carried out experiments with various protease inhibitors and significant inhibitory effect of AEBSF on the proteolytic activity of the HIB supernatant confirmed that serine proteases were present in the supernatant and that they were the ones responsible for S. aureus biofilm disruption [40].…”
Section: Role Of Extracellular Proteases From Other Prokaryotes In DImentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given that B. bacteriovorus has shown potential to protect crops and reduce biofouling [26][27][28][29], it would be useful to know how its effectiveness in structured habitats relates to its effectiveness as measured in well-mixed (unstructured) culture flasks [30][31][32]. In this regard, B. bacteriovorus has also attracted significant interest because of its potential to eradicate bacterial biofilms which are spatially structured at the microscale [33,34].…”
Section: Introductionmentioning
confidence: 99%